PENGARUH KEKURANGAN PROTEIN TERHADAP REMODELING TULANG ALVEOLUS (Eksperimental Aktivitas Osteoblas Dan Selosteoklas) - Pinandi Sri Pudyani (Faculty of Dentistry, Universitas Indonesia, 2015)
The aim of the study was to investigate the influence of protein deficiency on osteoblast and osteoclast cells activity on Sprague Dawley rats model alveolar bone. The study was carried out on 10 Spraque Dawley rats, divided in 2 groups. The first group was fed by died 4% protein after weaning period until animals aged 56 days. The other group was fed by standard diet. Osteoblas and osteoclast cells activity were counted by histological analysis. The result of the study from one-way Anova showed the significant differences (p<0,05) osteoblasts and osteoclasts activity between the protein deficiency group and the standard group.